SURVEI TINGKAT KAPASITAS OKSIGEN MAKSIMAL PEMAIN BULUTANGKIS PB SMASH KOTA MALANG - Achmad Furqon Bildhonny; I Nengah Sudjana; Rias Gesang Kinanti (Jurnal Sport Science, 2015)
ABSTRACT: This research aims at identifying the maximum oxygen uptake (VO2max) of Badminton Players of PB Smash Malang by measuring the player’s body capability in consuming maximum oxygen thorough Multistage Fitness Test. This research employs descriptive-quantitative method, by using survey approach. The research subject is badminton players of PB Smash Malang with the number of players is 25 people. In this research, instrument being used is Multistage Fitness Test which the result is converted in table of the VO2 Max rate prediction. Furthermore, the results will be categorized based on norm table of category. The result of the norm table is presented in accordance with the badminton players’ test achievement category. The result of Multistage Fitness Test shows that there are two players (8%) with Good category of maximum oxygen uptake (VO2 max), 6 players (24%) with Medium category of maximum oxygen uptake (VO2 max), 5 players (20%) with Poor category of maximum oxygen uptake (VO2 max), 12 players  (48%) with Very Poor category of maximum oxygen uptake (VO2 max) and no one or 0% with Superior and Very Good category of maximum oxygen uptake (VO2 max).Key Word: Maximum Oxygen Capacity (VO2 Max), Badminton Playrs of PB Smash Malang.